Pengaruh Earning Power, Kebijakan Dividen, dan Kepemilikan Manajerial Terhadap Manajemen Laba - Fitriani, Adinda Mellya; Fitriyana, Fina (Journal of Management Accounting, Tax and Production, 2024)
This study aims to determine the effect of earning power, dividend policy and managerial ownership on earnings management. This study uses a sample of LQ45 companies listed on the Indonesia Stock Exchange in 2019-2023. The sampling method used in this study is purposive sampling method using Eviews 13 for data analysis. The data source in this study is quantitative data derived from annual financial reports with 8 companies that were used as research samples with 5 years of observation, so that the total research sample was 40 samples. The analysis technique used is panel data regression. The results of this study indicate that simultaneously Earning Power, Dividend Policy and Managerial Ownership affect Earnings Management. Partial research results obtained that the Earning Power variable has no effect on Earnings Management. Partially, the Dividend Policy variable has no effect on Earnings Management, and partially the Managerial Ownership variable has a positive effect on Earnings Management.